A harmonized framework to assess coastal erosion blending copernicus marine data products and satellite imagery along Greek and Italian shorelines - Zachopoulos, Konstantinos; Kokkos, Nikolaos; Dal Barco, Maria Katherina; Furlan, Elisa; Pham, Hung Vuong; Torresan, Silvia; Critto, Andrea; Sylaios, Georgios (Frontiers in Environmental Science, 2025)
Coastal zones face intensified natural and anthropogenic disturbances, including rising sea levels, coastal erosion, and over-exploitation of resources. Coastal zone monitoring of these effects involves satellite-borne shoreline extraction and detection of change rates over time. Shoreline evolution is directly related to waves, tides, winds, storms, extreme events, sea level change, and human activities affecting the geomorphologic processes of the coast. The shoreline evolution along the study sites (Iera Poli of Messolonghi, Greece, and Ugento Municipality, Italy) was examined and assessed by analyzing historical satellite images, covering the area during the latest decade (2009–2019). The study focuses on eight geographical sub-areas. The areas were selected based on their high economic and aesthetic values and the potential vulnerability to coastal erosion and climate change impact, as identified by previous studies. The outcome of this analysis offers a useful decision support tool for screening and designing multi-layered adaptation strategies that integrate environmental conservation, coastal protection, and socioeconomic sustainability to enhance long-term coastal resilience.